2019
DOI: 10.1037/com0000184
|View full text |Cite
|
Sign up to set email alerts
|

Inferential reasoning in the visual and auditory modalities by cotton-top tamarins (Saguinus oedipus).

Abstract: Nonhuman primate species appear to vary markedly in inferential reasoning abilities as measured by a classic inference-by-exclusion cup task. Even within species, individuals who can solve the cup task in the visual domain often struggle to use analogous auditory cues. Here we tested five cotton-top tamarins (Saguinus oedipus), cooperatively breeding New World monkeys that use both visual and auditory information when foraging, to investigate whether they might be able to solve the inference-by-exclusion task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
1
2
1
Order By: Relevance
“…When partial information was presented revealing which cup was empty (exclusion cue), the tamarins could select the baited cup significantly more when auditory cues were used (i.e., noiseless shaking) and could use visual absence cues by the last two sessions, but did not use them well at the beginning of testing. These results stand in contrast to the former study with tamarins (Heimbauer et al, 2019), in which most tamarins demonstrated a failure to use auditory cues to find the baited cup either when it indicated where the food was (auditory present) or where the food was not (auditory absent). It is important to note here that we used a different training methodology—our subjects were exposed to the visual and auditory stimuli presented as a compound stimulus and were presented trials that displayed both together until they were responding at a fairly high accuracy (nine out of 12 trials within a single session, or 75% correct).…”
Section: Discussion and Experimentscontrasting
confidence: 99%
See 2 more Smart Citations
“…When partial information was presented revealing which cup was empty (exclusion cue), the tamarins could select the baited cup significantly more when auditory cues were used (i.e., noiseless shaking) and could use visual absence cues by the last two sessions, but did not use them well at the beginning of testing. These results stand in contrast to the former study with tamarins (Heimbauer et al, 2019), in which most tamarins demonstrated a failure to use auditory cues to find the baited cup either when it indicated where the food was (auditory present) or where the food was not (auditory absent). It is important to note here that we used a different training methodology—our subjects were exposed to the visual and auditory stimuli presented as a compound stimulus and were presented trials that displayed both together until they were responding at a fairly high accuracy (nine out of 12 trials within a single session, or 75% correct).…”
Section: Discussion and Experimentscontrasting
confidence: 99%
“…The data supported their use of both visual and auditory cues to respond correctly. This extends the prior research on tamarins which suggested that they were more able to find the baited cup with visual cues than auditory ones (Heimbauer et al, 2019). By first exposing subjects to both visual and auditory cues to represent the presence of food, the tamarins may have been able to learn the auditory cues that signaled the presence of food through exposure such that they could use each individual cue, like elements of a compound stimulus, to find the food.…”
Section: General Discussion and Conclusionsupporting
confidence: 87%
See 1 more Smart Citation
“…Inferential reasoning refers to the capacity to integrate indirect information regarding an event or stimulus to form inferences, enabling animals to better cope with novel challenges (Heimbauer et al 2019). Solutions must be reached without explicit learning and are assumed to be particularly advantageous in unstable, but predictable physical or social environments (Völter andCall 2017, Nawroth et al 2019).…”
Section: Inferential Reasoningmentioning
confidence: 99%